Peer-based dental composite training course - Maximilian Dobbertin; Stefan Rüttermann; Susanne Gerhardt-Szép (Journal of Dental Problems and Solutions - Peertechz Publications, 2019)
This multivariate, prospective, monocentric, observational pilot study evaluates the experimental acceptance and feasibility of a peer-based course concept. Those both theoretical and practical workshops were offered to dentistry students in all clinical semesters on a voluntary basis. In 9 courses a total of 45 students took part in small learning groups (n = up to 12 students). For the evaluation a questionnaire was used, which was divided into 4 domains, the competence acquisition consisting of 4 items (A), the acceptance of the course concept with 7 items (B), the framework conditions with 3 items (C) and the recommendation with 2 items (D). The rating was based on a scale of grades (1 = "very good" to 5 = "poor"). In the assessment of the acceptance of the course concept, the following results were obtained in 4 domains: In "A" the subjective optimization of manual skills increased by 0.49 ± 0.86 and the theoretical skills improved by 1.32 ± 0.60 grades. "B" being dived into the subcategories as presentation 1.26 ± 0.34; speaker 1.17 ± 0.21; visual models 1.26 ± 0.28; case examples 1.22 ± 0.24; theoretical advices 1.20 ± 0.22; practical implementation tips 1.18 ± 0.22; practical demonstration 1.22 ± 0.28. The framework conditions "C" were subdivided into spatiality 1.34 ± 0.39; duration of the course 1.97 ± 0.34; media 1.32 ± 0.40. "D" being stated as the overall grading of 1.24 ± 0.23 and the innovation of the teaching concept of 1.31 ± 0.33 suggest a high acceptance of the short concept. About 55% of the course participants evaluated in the free text like to have had more time to deepen their skills with individual care even more. 84% would be interested in a sequel. An improvement could be assessed by the peer-tutor as they began to get comfortable and more advanced with the composite materials and dental instruments for texturing and polishing used in the course.  The results indicate that extracurricular free courses offered by students to students may well be a useful addition to university settings. It therefore makes sense to support suitable students by teaching staff and, where appropriate, to train in the training of third so that the knowledge can be shared more easily with each other. Through the small learning groups, the skills could be taught more effectively in theoretical and practical terms and it could be targeted to the individual needs of the participating students.